The Development of Strategies to Teach Listening and Speaking Skills to English Second Language (ESL) Learners in African Society: Insight from the Pinetown District, KwaZulu Natal - Mthembu, Bheki; Pillay, Pravina (International Journal of Criminology and Sociology, 2021)
Listening and speaking proficiently in English Second Language teaching is a perennial problem in South Africa. While scholars in the domain of ESL acknowledge that there is a severe challenge with teaching listening and speaking skills, there is a shortage of literature in this sphere. Although English is not the home language for most Black learners in South Africa, they are compelled to use English as the Language of Learning and Teaching (LoLT). This serves as a hindrance in developing learner’s proficiency in listening and speaking, which is further exacerbated by poor ESL teaching performed by teachers whose own ESL proficiency is limited. This paper seeks to explore the strategies used by teachers to teach listening and speaking skills to ESL Grade eleven learners’ in selected township schools in the Pinetown District, KwaZulu Natal. Township, in South Africa, refers to racially segregated and often underdeveloped urban areas created for people of color during the apartheid regime. Data was generated using individual semi-structured interviews with eight participating teachers and observation of classroom lessons and document analysis. A significant finding revealed that the claims made by the ESL teachers about their pedagogical practices tallied with the requirements of the Continuous Assessment Policy Statement (CAPS) and their lesson plans but contradicted the ESL teachers’ actual practice in the classroom.